The Influence of Capital Structure, Free Cash Flow, Inflation and Dividend Policy on Company Value with CSR as a Moderator - Made Aprilia Vitriyanti; Henny Rahyuda (PT. Publikasiku Academic Solution, 2025)
The main goal of a company is to increase its firm value by maximizing its share price. The higher the firm value, the higher the stock value will be. The construction and building subsector is one of the key sectors supporting economic growth in Indonesia. However, The growth and increase in the number of companies is not accompanied by an increase in the value of companies in the construction and building sub-sector in Indonesia. This study aims to examine the effect of capital structure, free cash flow, and inflation on firm value through dividend policy, with Corporate Social Responsibility (CSR) as a moderating variable. The data analysis techniques used in this study are Path Analysis and Moderated Regression Analysis (MRA) with the help of SPSS version 27. The results indicate that capital structure has a negative and significant effect on firm value, while Free Cash Flow (FCF), inflation, and dividend policy have a positive and significant effect on firm value. Capital structure does not affect dividend policy, while FCF and inflation have a positive and significant effect on dividend policy. Dividend policy mediates the effect of FCF an inflation on firm value but does not mediate the effect of capital structure. CSR strengthens the relationship between dividend policy and firm value. The results of this study are expected to help companies in evaluating factors that can increase firm value in the future, help investors to pay attention to factors that influence firm value as a basis for making investment decisions, and for future researchers it is hoped that they can add other macroeconomic variables by considering more diverse companies in terms of industrial sectors.